Implementation of a Dynamo Revit-Based Approach to Earned Value Identification Mechanism - Gabriel Hotasi Stieward; I Nyoman Dita Pahang Putra (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
The rapid development of the construction industry in Indonesia, reflected in the increasing volume of projects, growing design complexity, and higher demands for efficiency, requires effective project planning and control to ensure that implementation proceeds efficiently and sustainably, supporting better construction production performance. However, schedule delays and cost overruns remain two major issues frequently encountered in construction projects, particularly when planning, execution, and control processes are not optimally integrated. This study aims to implement Building Information Modelling (BIM) 5D as a tool for monitoring project time and cost, in combination with the earned value management method, during the construction of the Ambengan Batu Multipurpose Building. The project’s 3D model was developed in Autodesk Revit and subsequently linked to scheduling and cost data via visual programming in Dynamo. EVM values including Planned Value, Earned Value, and Actual Cost were calculated to obtain performance indicators such as Schedule Variance, Cost Variance, Schedule Performance Index, and Cost Performance Index. All analytical results were then visualized using a color-coding system applied to the BIM model elements, enabling project performance conditions to be quickly and effectively interpreted. The findings of this study are expected to demonstrate that integrating BIM 5D with EVM provides more accurate, transparent, and easily evaluated monitoring of project time and cost than conventional methods. This approach has been shown to enhance the effectiveness of project control, support sustainable construction practices, improve project production efficiency, and offers significant visual support for decision-making.Contribution to Sustainable Development Goals (SDGs):SDG 9: Industry, Innovation and InfrastructureSDG 11: Sustainable Cities and CommunitiesSDG 12: Responsible Consumption and Production